Strategi Komunikasi Digital Pada Komunitas Nabung Jalanan Ngawi dan Implikasinya Dalam Program Filantropi Sosial - Rahmawati, Alfiana Yuniar; Nurchayati, Zulin (Metta : Jurnal Ilmu Multidisiplin, 2024)
Digitalization is the key to the growth of a civilization that cannot be ignored. This is because the demands for mastery and use of technology for individuals and organizations are becoming increasingly real due to digital-based market changes. The emergence of digital communication media which is closely related to the internet, has become an active space for people to convey information, receive aspirations and ideas, and be able to offer new, more professional ways. One form of activity that utilizes digital communication media as the main media is social philanthropy activities initiated by the Ngawi Street Savings community. Since 2020, Nabung Jalanan Ngawi has been in existence carrying out social philanthropy actions for street people in the Ngawi Regency area. The aim of this research is to find out what digital communication strategies are carried out by Nabung Jalanan Ngawi and what the implementation process is in social philanthropy programs. This research also uses qualitative methods with a case study approach. The research results show that the key to the success of the digital communication strategy carried out by Nabung Jalanan Ngawi is consistency in posting every donation and activity pamphlet as well as strength in maximizing content management. The use of digital media can make branding Nabung Jalanan Ngawi easier for the wider community. This can support the process of implementing social philanthropy activities to be more systematically planned. The social philanthropy activities that have been carried out by the Nabung Jalanan Ngawi community include sharing free food, distributing suitable clothing to orphanages, distributing free takjil in the month of Ramadhan, and raising funds when a disaster occurs in an area. Nabung Jalanan Ngawi Community utilizes digital media to support the goals of social philanthropy programs to run optimally and evenly.